Aryl hydrocarbon receptor polymorphisms are associated with dry skin phenotypes in Chinese patients with atopic dermatitis. (29th November 2018) - Li, Z. Z.; Zhong, W. L.; Hu, H.; Chen, X. F.; Zhang, W.; Huang, H. Y.; Yu, B.; Dou, X.
Summary: Background: Epidermal barrier dysfunction is the initial event in the development of atopic dermatitis (AD). Recent studies have identified a crucial role for the aryl hydrocarbon receptor (AHR) in controlling the gene expression of filaggrin and other skin barrier proteins, suggesting an underlying association between AHR and AD pathogenesis. Aim: To investigate the role of AHR gene polymorphisms in the susceptibility to AD and in AD‐associated phenotypes. Methods: We enrolled 487 patients with AD, 210 patients with psoriasis and 226 healthy controls (HCs) from the Han Chinese population, and genotyped two AHR single‐nucleotide polymorphisms (rs10249788 and rs2066853) by PCR and subsequent DNA sequencing. Results: The AHR rs10249788 and rs2066853 polymorphisms were found in both sets of patients (AD and psoriasis) and in HCs, but no significant differences were detected in genotype or allele frequencies between the three groups. However, patients with AD with the rs10249788 (CT/TT) or rs2066853 (AG + AA) genotype were more likely to have severe dry skin scores. In the stratification analysis, the AHR rs2066853 (AG + AA) and rs10249788 (CT + TT) genotypes could predict a higher risk of severe dry skin phenotypes in the male, early‐onset and allergic rhinitis subgroups. Furthermore, the combined rs10249788 (CT + TT) and rs2066853 (AG + AA) genotypes led to a higher risk for severe dry skin in patients with AD. Conclusion: AHR polymorphisms are not associated with the risk of AD; however, they may predict a dry skin phenotype in patients with AD.